2019
DOI: 10.7717/peerj.7722
|View full text |Cite
|
Sign up to set email alerts
|

CD36 identified by weighted gene co-expression network analysis as a hub candidate gene in lupus nephritis

Abstract: Lupus nephritis (LN) is a severe manifestation of systemic lupus erythematosus (SLE), which often progresses to end-stage renal disease (ESRD) and ultimately leads to death. At present, there are no definitive therapies towards LN, so that illuminating the molecular mechanism behind the disease has become an urgent task for researchers. Bioinformatics has become a widely utilized method for exploring genes related to disease. This study set out to conduct weighted gene co-expression network analysis (WGCNA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…They found that LN-related genes were mainly involved in immune and inflammatory responses, which are in agreement with what we found. Likewise, the GSE104948 dataset was analyzed by WGCNA, and CD36 was ultimately screened out as a hub gene of the pathogenesis of LN ( 45 ). However, neither of their findings have been validated in LN patients.…”
Section: Discussionmentioning
confidence: 99%
“…They found that LN-related genes were mainly involved in immune and inflammatory responses, which are in agreement with what we found. Likewise, the GSE104948 dataset was analyzed by WGCNA, and CD36 was ultimately screened out as a hub gene of the pathogenesis of LN ( 45 ). However, neither of their findings have been validated in LN patients.…”
Section: Discussionmentioning
confidence: 99%
“…Modules that are highly relevant to clinical trait are further analyzed and crucial transcripts are identified. WGCNA has been proven to be useful in various types of diseases, such as cancer 11 , immune disease 12 , chronic disease 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Weighted gene coexpression network analysis (WGCNA) is a bioinformatics analysis tool based on the hypothesis that the biological expression pattern of genes obeys the characteristics of a scale-free network, and the central factors in the network would be more easily found out when the coexpression relationships are weighted [3]. The technique has been broadly used to explore new hub candidate genes, biomarkers, or therapeutic targets in various kinds of diseases including acute diseases, chronic diseases, infectious diseases, and tumors [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%